Board Members in the Service Industry: An Empirical Examination of the Relationship Between Corporate Social Responsibility Orientation and Directorial Type - Ibrahim, Nabil A. (Journal of business ethics, 2003)
One area of business performance of particular interest to both scholars and practitioners is corporate social responsibility. The notion that organizations should be attentive to the needs of constituents other than shareholders has been investigated and vigorously debated for over two decades. This has provoked an especially rich and diverse literature investigating the relationship between business and society. As a result, researchers have urged the study of the profiles and backgrounds of corporate upper echelons in order to better understand this relationship., There is ample evidence that corporations have in recent years increased the proportion of outside directors on their boards. This has been partly in reaction to increased interest in the corporate social responsiveness of business organizations and suggestions that the board of directors could play a unique role in this area. The expectation on the part of practitioners, researchers, and governmental regulators is that outside directors will advocate greater corporate responsiveness to society's needs by playing a more active role in overseeing managerial decisions., The purpose of this study is to partially fill a void in the literature by determining whether or not these expectations are justified, particularly in the service industry. Data were collected as part of a larger cross-national study of corporate social responsibility. A multivariate analysis of variance (MANOVA) of the results of a survey of 307 board members (198 outside and 109 inside directors) indicates that outside directors exhibit greater concern about the discretionary component of corporate responsibility and a weaker orientation toward economic performance. No significant differences between the two groups were observed with respect to the legal and ethical dimensions of corporate social responsibility. Some explanations as well as limited generalizations and implications are developed.